Morphological Characteristics, Classifications and Difficulties in the Use of Diagnostic Criteria for Serrated Lesions of the Large Intestine - Bastos Junior,Cesar de Souza (2021)
Abstract Introduction Colorectal carcinoma (CRC) is the most common gastrointestinal neoplasm in the world, accounting for 15% of cancer-related deaths. This condition is related to different molecular pathways, among them the recently described serrated pathway, whose characteristic entities, serrated lesions, have undergone important changes in their names and diagnostic criteria in the past thirty years. The multiplicity of denominations and criteria over the last years may be responsible for the low interobserver concordance (IOC) described in the literature. Objectives The present study aims to describe the evolution in classification of serrated lesions, based on the last three publications of theWorld Health Organization (WHO) and the reproducibility of these criteria by pathologists, based on the evaluation of the IOC. Methods A search was conducted in the PubMed, ResearchGate and Portal Capes databases, with the following terms: sessile serrated lesion; serrated lesions; serrated adenoma; interobserver concordance; andreproducibility.Articlespublished since 1990were researched. Results and Discussion The classification of serrated lesions in the past thirty years showed different denominations and diagnostic criteria. The reproducibility and IOC of these criteria in the literature, based on the kappa coefficient, varied in most studies, from very poor to moderate. Conclusions Interobserver concordance and the reproducibility of microscopic criteria may represent a limitation for the diagnosis andappropriatemanagementof these lesions. It is necessary to investigate diagnostic tools to improve the performance of the pathologist’s evaluation, for better concordance, and, consequently, adequate diagnosis and treatment.